Analisis Strategi Segmntation, Targeting, dan Positioning dalam Mengingkatkan Volume Penjualan pada Kedai Kopi Roemah Aki’q Surabaya - Daru Teja Sasangka; Acep Samsudin (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research employs a qualitative descriptive method with the aim of understanding the segmentation, targeting, and positioning strategies to enhance sales volume at "Kedai Kopi Roemah Aki’q" in Surabaya. The subjects of the study include the owner, employees, and consumers. Data collection techniques include in-depth interviews, observations, and documentation. Based on the research findings, segmentation is focused on the northern part of Surabaya with consumers aged 17-30, including adolescents and young adults, both male and female, belonging to the lower-middle class. Their behavior includes a fondness for hanging out, socializing with friends, playing games, and completing tasks. Targeting is aimed at adolescents to young adults, both male and female, aged 17-30, utilizing social media promotion and leveraging the services of content creators. Product specialization involves offering unique and distinctive menus. Positioning adopts a vintage concept, presenting menus inspired by the past, prioritizing consumer needs and desires, providing affordable prices, and maintaining the highest quality.